Anthropometric parameters of amateur boxers: Comparability and sensitivity of equations used to calculate body density - Davis, P.; Beneke, R. (Journal of Combat Sports and Martial Arts, 2016)
Introduction. The comparability and validity of equations used to calculate body density and body fat in boxers is unknown. Material and methods. Twenty-one amateur boxers covering all 10 weight categories had seventeen anthropometric measurements taken. Comparison was made between four different percentage body fats based on different body density equations and five different sum of x values. Results. The results suggest that low and medium-weight boxers are similar in terms of morphological (mesomorph-ectomorph) and anthropometric characteristics, contrasting against the `different breed` of the high-weight group (mesomorph-endomorph). Results from different body density equations differ by as much as 7.6%. The body density equation of Lohman is the most reliable at detecting differences between weight groups. Conclusion. Priority should be given to measuring subscapular, abdominal and thigh skin folds as they have largest variation between weight categories. Using the sum of 6a (triceps, subscapular, bicep, iliac crest, abdominal and thigh) as opposed to the total sum of 8 improves data collection speed, comparability and validity when making comparisons over time and between boxers. The use of a body fat percentage should only be use as a last resort for feedback of results in layman`s terms and its limitations made clear.